1998
DOI: 10.1074/jbc.273.14.8232
|View full text |Cite
|
Sign up to set email alerts
|

MKK6 Activates Myocardial Cell NF-κB and Inhibits Apoptosis in a p38 Mitogen-activated Protein Kinase-dependent Manner

Abstract: In cardiac myocytes the stimulation of p38 mitogenactivated protein kinase activates a hypertrophic growth program and the induction of the cardiac-specific genes associated with this program. This study focused on determining whether these novel growth-promoting effects are accompanied by the p38-mediated inhibition of apoptosis, and if so, what signaling pathways might be responsible. Primary neonatal rat ventricular myocytes were driven into apoptosis by treatments known to induce apoptosis in other cell ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
140
2
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 210 publications
(149 citation statements)
references
References 74 publications
6
140
2
1
Order By: Relevance
“…Similarly, activation of p38 seems to be involved in programmed cell death in a variety of cell types upon various apoptotic stimuli (Kummer et al, 1997;Mackay and Mochly-Rosen, 1999;Oh-hashi et al, 1999). However, there are also reports that do not support this view (Zechner et al, 1998;MacFarlane et al, 2000).…”
Section: Introductionmentioning
confidence: 71%
“…Similarly, activation of p38 seems to be involved in programmed cell death in a variety of cell types upon various apoptotic stimuli (Kummer et al, 1997;Mackay and Mochly-Rosen, 1999;Oh-hashi et al, 1999). However, there are also reports that do not support this view (Zechner et al, 1998;MacFarlane et al, 2000).…”
Section: Introductionmentioning
confidence: 71%
“…There is conflicting evidence for the role of p38/MAPK in influencing cell survival of cisplatin-treated cells. For example, studies have suggested that over expressing an active form of the p38/MAPK activator MKK6 protects cardiac myocytes from treatment with anisomyc [42]. Similarly, early activation of p38/MAPK is necessary and sufficient to protect Kym cells from tumour necrosis factor-α-mediated apoptosis [43], and expression of the p38/MAPK attenuates cell death induced by Fas ligand and UV light [44].…”
Section: Muscella Et Al -Role Of Egfr In Cisplatin-treated Cells -16mentioning
confidence: 99%
“…This plays a central role in promoting survival in NIH 3T3 cells (Demarchi et al, 2001). MKK6 activates myocardial cell NF-κB and inhibits apoptosis in a p38 mitogen-activated protein kinase dependent manner (Zechner et al, 1998). Limb girdle muscular dystrophy type 2A results in a decreased production of calpain 3.…”
Section: Anti-apoptotic Effects Of Nf-κbmentioning
confidence: 99%